Dataset on optical characteristics and spectroscopic indices of dissolved organic matter of the Kara, Laptev, and East Siberian seas in August–September 2017 - Anastasia N. Drozdova; Marat S. Puiman; Ivan N. Krylov; Svetlana V. Patsaeva; Alexander V. Shatravin (Data in Brief, 2019)
A total of 137 water samples to study optical properties of chromophoric dissolved organic matter were collected in the Artic shelf seas during the 69th cruise on board the R/V Akademik Mstislav Keldysh in August–September 2017. Sampling sites were located in the Kara, Laptev and East Siberian seas and associated to the areas influenced by terrestrial runoff of the Kolyma, Indigirka, Lena, Khatanga, Ob and Yenisei rivers. In this data article, conventional spectroscopic indices and lignin phenol concentrations, calculated on the basis of fluorescence and UV–vis absorption spectra, are presented. Keywords: Dissolved organic matter, Fluorescence, Absorbance, Spectroscopic indices, Arctic